2015
DOI: 10.2174/1570159x13666151102103305
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoids Derived From Arachidonic Acid and Their Family Prostaglandins and Cyclooxygenase in Psychiatric Disorders

Abstract: Arachidonic acid (AA)-derived lipid mediators are called eicosanoids. Eicosanoids have emerged as key regulators of a wide variety of physiological responses and pathological processes, and control important cellular processes. AA can be converted into biologically active compounds by metabolism by cyclooxygenases (COX). Beneficial effect of COX-2 inhibitor celecoxib add-on therapy has been reported in early stage of schizophrenia. Moreover, add-on treatment of celecoxib attenuated refractory depression and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 93 publications
0
66
0
1
Order By: Relevance
“…control i.e., from 2.4 fold at 50 nM to 9.0 fold at 500 nM. Increased expression of selenoproteins, including GPx1 is known to mitigate inflammation and bolster immunity that involves down-regulation of COX-2 and mPGES-1, while upregulating H-PGDS to effect a process called “eicosanoid class switching mechanism” in Se stimulated RAW264.7 cells (Yui, Imataka, Nakamura, Ohara, & Naito, 2015; Duntas, 2009; Vunta et al, 2007). Higher Se supplementation up to 2 µM in the form of sodium selenite is also reported to inhibit NFκB-dependent transcription (Nettore et al, 2017; Meplan et al, 2016; Youn et al, 2008; Maehira, Mivagi, & Eguchi, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…control i.e., from 2.4 fold at 50 nM to 9.0 fold at 500 nM. Increased expression of selenoproteins, including GPx1 is known to mitigate inflammation and bolster immunity that involves down-regulation of COX-2 and mPGES-1, while upregulating H-PGDS to effect a process called “eicosanoid class switching mechanism” in Se stimulated RAW264.7 cells (Yui, Imataka, Nakamura, Ohara, & Naito, 2015; Duntas, 2009; Vunta et al, 2007). Higher Se supplementation up to 2 µM in the form of sodium selenite is also reported to inhibit NFκB-dependent transcription (Nettore et al, 2017; Meplan et al, 2016; Youn et al, 2008; Maehira, Mivagi, & Eguchi, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, ω-6 PUFAs are associated with in ammatory responses, constriction of blood vessels, and platelet aggregation [43]. In contrast, ω-3 PUFAs show anti-in ammatory and pro-resolving activities to resolve in ammation effectively, and alter the function of vascular and carcinogen biomarkers, thus reducing the risk of cancer [44,46,47]. Considering that malaria is known as an in ammatory disease, with recognized symptoms, such as fever and headache, signs, such as splenomegaly, and damage in other organs such as liver and kidney [8], the ndings in this study corroborated with those assessments, since all LMs found on signi cantly higher concentrations compared to the controls are from ω-6 pathway (AA and LA pathways, Table 2), while the lipids found at remarkably lower concentrations comparing to the controls are related to ω-3 pathway (EPA and DHA pathways, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…ПГ не являются медиаторами боли. Однако они повышают чувствительность ноцицептивных рецепторов (сенсиби-лизируют их) к медиаторам боли, которыми являются гистамин и брадикинин [7].…”
Section: клиническое наблюдениеunclassified